Code Switching and Code Mixing K-Poppers Exol in Social Media Twitter - Dian Wulandari; Eka Susylowati (Faculty of Language and Literature, University of Surakarta, 2021)
The research is conducted in order to describe the types of code switching and code mixing K-Popers in the social media twitter. The purpose of this study is to get some information on the types of code mixing and code switching frequently used by K-Popers EXOL. The technique of collecting data is observation, documentation method, and questionnaire. The researcher used triangulation as technique of analyzing data. Source of the data are taken from Twitter written by K-Popers EXOL. The data of this data research are comments, videos and photo statements posted by EXOL in social media Twitter from February – June 2021. The research finding shows three types of switching codes, they are Inter-sentential switching, Intra-sentential switching and emblematic switching. The most dominated code switching is inter-sentential switching (24 data). And, two types of code mixing are intern code mixing and extern code mixing. The most dominated of code mixing is extern code mixing with 27 data from 41 total data. In this research, none of intern code mixing are found.